Seleksi Galur-Galur Leuconostoc yang Mempunyai Aktivitas Bakteriostatin Terhadap Berbagai Bakteri Indikator - Retnaningsih, Agustina; Malik, Amarila; Radji, Maksum (Majalah Ilmu Kefarmasian, 2012)
Lactid Acid Bacteria (LAB) are known to produce bacteriocins which have antimicrobial activity, and possessed to be developed as antibiotic complement. This study aimed to characterize bacteriocins activity from Leuconostoc strains isolated previously from local sources, and to optimize pH and incubation temperature as well. A well diffusion agar assay for zone inhibition method and bacteriocin potency assay performing minimum inhibition concentration (MIC) have been done. Bacterial indicators used in this study are Leu. mesenteroides TISTR 120, and JCM 6124, Staphylococcus aureus FNCC 0047, Listeria monocytogenes FNCC 0156, Escherichia coli FNCC 0183, Pseudomonas aeruginosa FNCC 0063, Salmonella typhi FNCC 0165 and Bacillus subtilis FNCC 0061. Catalase, Trypsin and Protease K were also used for confirmation test. Results revealed that both Leu. mesenteroides MBF2-5 and MBF7-17 possessed bacteriocin activity although against Leu. mesenteroides TISTR 120 and JCM 6124 indicators strains. The optimum pH for bacteriocin potency assay for both Leuconostoc strains MBF2-5 and MBF7-17 was pH 6, whereas the optimum incubation temperature was 32 oc with MIC value of 90% and 80%, respectively.